Role Play and Simulation-Based Learning Model in Practical Exams for Sermons and Lectures - Gun Gun Gunawan; Fitriyani Kosasih (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study investigates the collaboration between Islamic Religious Education (PAI) and Pancasila and Civic Education (PPKn) teachers through the implementation of the Role Play and Simulation-Based Learning (SBL) model at SMK Husein Sastranegara Bandung. The research employs a descriptive qualitative approach, utilizing interviews, observations, and document analysis to explore the impact of this collaborative pedagogical strategy on student engagement, self-efficacy, and the internalization of Islamic and civic values. Findings reveal that structured teacher collaboration significantly enhances student participation, reduces passivity, and fosters a meaningful learning environment. Students demonstrate increased confidence and communicative competence through experiential learning, effectively bridging theoretical knowledge with real-life applications. The study contributes valuable insights into the effectiveness of integrative teaching methods in vocational education, offering actionable recommendations for educators and policymakers to promote holistic character development and civic consciousness.